Strain differences in systematic 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine neurotoxicity in mice correlate best with monoamine oxidase activity at the blood-brain barrier - Riachi, Naji J. (1988)
We measured monoamine oxidase activity in the cerebral cortex, striatum and brain microvessels of two mouse strains that differ in their susceptibility to systemic 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPIP) neurotoxicity using specific pargyline binding and the rate of MPTP oxidation ir. vitro . We correlated these measurements with the results of it. vivo experiments on: (i) the effect of MPTP on the striatal content of dopamine and its metabolites, and (ii) the regional brain accumulation of MPTP and its metabolites after systemic administration of tritiated MPTP. Results of the ir. vivo experiments do not correlate well with monoamine oxidase activity in the cerebral cortex and striatum, but correlate well with the inverse of monoamine oxidase activity in brain microvessels from the two strains of mice. These results support our hypothesis that monoamine oxidase activity in brain microvessels have an important role, as part of the “biochemical” blood-brain barrier, in obstructing MPTP entry into the brain.